Oxytocin and Psychological Factors Affecting Type 2 Diabetes Mellitus. (10th September 2012) - Kontoangelos, K.; Raptis, A. E.; Papageorgiou, C. C.; Tsiotra, P. C.; Papadimitriou, G. N.; Rabavilas, A. D.; Dimitriadis, G.; Raptis, S. A.
Abstract : Background . The aim of this study was to investigate the association of oxytocin with trait and state psychological factors in type 2 diabetic patients. Methods . OXT and psychological variables were analyzed from 86 controlled diabetic patients (glycosylated haemoglobin A1c (HbA1c) < 7%) from 45 uncontrolled diabetic patients (HbA1c ≥ 7). Psychological characteristics were assessed with the Eysenck Personality Questionnaire (EPQ), while state psychological characteristics were measured with the Symptom Checklist 90-R (SCL 90-R). Blood samples were taken for measuring oxytocin in both subgroups during the initial phase of the study. One year later, the uncontrolled diabetic patients were reevaluated with the use of the same psychometric instruments. Results . During the first evaluation of the uncontrolled diabetic patients, a statistically significant positive relationship between the levels of OXT and psychoticism in EPQ rating scale (P < 0.013 ) was observed. For controlled diabetic patients, a statistically significant negative relationship between oxytocin and somatization (P < 0.030 ), as well as obsessive-compulsive scores (P < 0.047 ) in SCL-90 rating scale, was observed. During the second assessment, the values of OXT decreased when the patients managed to control their metabolic profile. Conclusions . The OXT is in association with psychoticism, somatization, and obsessionality may be implicated in T2DM.